Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Please be clear with the answer thank you bye-bye bye-bye

Please Be Clear With The Answer Thank You Byebye Byebye class=

Sagot :

Solve the system of equations:

3x + 3y = 3

5x + y = 13

Solving the second equation for y:

y = 13 - 5x

Substituting in the first equation:

3x + 3(13 - 5x) = 3

Opeating:

3x + 39 - 15x = 3

Simplifying:

-12x + 39 = 3

Subtracting 39:

-12x = -36

Dividing by -12:

x = -36 / (-12)

x =3

Substituting in the equation for y:

y = 13 - 5(3)

y = -2

Answer: x = 3, y = -2

View image AmberlyL569906